"Earth to Luna!" as a mediating educational tool in Science teaching in the initial grades of Elementary School - Bianca Gomes de Souza; Dirce Aparecida Foletto de Moraes (Universidade Federal do Oeste da Bahia, 2020)
The research attempted to explore contributions of the Earth to Luna! cartoon as a didactic strategy to mediate Science teaching in the initial grades of Elementary School. Through data collection, theoretical subsidy was inquired in articles related to Science teaching and the usage of cartoons as an educational resource. As a methodological approach, this study was established as qualitative, in the exploratory-explanatory approach, besides using content analysis. The results acquired were ordered according to the curriculum of Brazil's National Common Curricular Base (BNCC), which organizes the Science areas in three thematic units, all of them incorporated on Earth to Luna!. Therefore, it is concluded the cartoon is qualified as a pedagogical mediator in Science teaching, being a didactic alternative to mediate education, as well as assisting with the current scenario represented by the Covid-19 pandemic, since using technologies as mediators is primordial for distance learning.